INFLUENCE OF DEMOGRAPHIC, ANAMNESTIC AND ANTHOPOMETRICAL CHARACTERISTICS ON AFFECTIVE STATUS OF OPIOID ADDICTED PATIENTS - Druz', O.V. (World of Medicine and Biology, 2012)
It was studied demographic, anamnestic and anthopometrical characteristics of 270 opioid addicted patients and 270 persons without signs of any dependence. Then, by means of three widespread psychometric tools (scale Hamіlton-21, MADRS and HADS) current affective status of responders was investigated - twice (before and after detoxication) for opioid addicted persons, and once for persons without signs of any dependence. The correlation analysis of relation between demographic, anamnestic and anthopometrical characteristics with indicators of the actual affective status was carried out. It is shown, that asthenic constitutionally-morphological type is the factor of predisposition to affective disorders of depressive circle in opioid addicted patients. Inverse correlation between the duration of drug use experience and doses of opioids with symptoms of depression during detoxication are revealed, that can be a consequence of adaptation of patients to their disease.